Unlimited Energy Source: A Review of Ocean Wave Energy Utilization and Its Impact on the Environment - Muhammad Satriawan; L Liliasari; Wawan Setiawan; Ade Gafar Abdullah (Universitas Pendidikan Indonesia, 2021)
This paper aims to review the potential of wave energy in several countries, the wave energy converter technology that has been developed, and the impact of the installation of wave energy converter technology devices on the environment. In addition, it discusses the theoretical formulations and challenges in the development of energy converter technology in the future. Based on the detail analysis, the potential of ocean wave energy for alternative energy is very large but cannot be used optimally because the technology of wave energy converter that has been developed is still on a prototype scale. In addition, the impact of the use of ocean wave converters on the environment is insignificant compared with conventional energy. Finally, this study informs and recommends the government and the private sector to start investing in the ocean wave energy industry optimally in order to achieve a sustainable future.